A restorative justice approach to legalising unauthorised immigrants. Issue 1 (2nd January 2017) - Sullivan, Michael J.
ABSTRACT: In this paper, the author argues for a restorative justice approach towards regularising the status of long-term residents who entered a country without authorisation or overstayed their visas. Citizens have an interest in enforcing their immigration laws. However, the author questions the benefit of incarcerating and deporting long-term unauthorised immigrant residents who are willing to make amends for their immigration offences. Here, the author examines two possible applications of restorative justice processes as alternatives to deportation for immigration offences: victim–offender mediation where there is an individual victim who is directly harmed by an unauthorised immigrant's use of false documents; and community reparative boards to address the more diffuse harms arising from entering and remaining in a country without authorisation. As alternatives to detention and deportation, these processes may provide unauthorised immigrants an opportunity to make amends for immigration offences and further integrate into their adopted communities.